Upper-Extremity Deep Venous Thrombosis following a Fracture of the Proximal Humerus: An Orthopaedic Case Report. (4th November 2019) - Strony, John; Chang, Gerard; Krieg, James C.
Abstract : Deep venous thrombosis of the lower extremities following orthopaedic surgery is well-documented. Though less common than its lower extremity counterpart, upper extremity deep venous thrombosis (UEDVT) has been documented in the literature as well, largely in the context of arthroscopic shoulder surgery. However, there is a paucity of literature documenting UEDVT following surgical fixation of upper extremity fractures, specifically fractures involving the proximal humerus. We present a case of UEDVT following a fracture to the proximal humerus and subsequent surgery. Though UEDVT is considered a rare complication following this type of surgery based on a lack of documentation within the literature, we believe a high-index of suspicion is required to prevent potentially life-threatening sequelae, such as pulmonary embolism (PE) and post-thrombotic syndrome.